2006
DOI: 10.1002/dmrr.688
|View full text |Cite
|
Sign up to set email alerts
|

Decline of neuroadrenergic bronchial innervation and respiratory function in type 1 diabetes mellitus: a longitudinal study

Abstract: Neuroadrenergic denervation of the lung parallels the decline of respiratory function indexes in diabetic patients both with and without AN and seems to be independent from the quality of glycemic control.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(11 citation statements)
references
References 35 publications
1
10
0
Order By: Relevance
“…A recent study in lung function in a smaller group of type 1 diabetic patients followed up for a period of 5 years showed similar results regarding the time-related decline [98]. In these patients, a decline of 68 ml/year in FEV1 was observed, which was very similar to the results obtained in the previous study.…”
Section: Decline In Lung Function Over Time and Its Clinical Implicationsupporting
confidence: 86%
See 1 more Smart Citation
“…A recent study in lung function in a smaller group of type 1 diabetic patients followed up for a period of 5 years showed similar results regarding the time-related decline [98]. In these patients, a decline of 68 ml/year in FEV1 was observed, which was very similar to the results obtained in the previous study.…”
Section: Decline In Lung Function Over Time and Its Clinical Implicationsupporting
confidence: 86%
“…The FEV1 decline, unrelated to the quality of glycemic control, was almost equal in the subgroups of patients with or without autonomic neuropathy. Also, it affected other functional parameters, such as DLCO and neuroadrenergic bronchial innervation, measured by lung ventilation scintigraphy with MIBG [98]. Table 2 shows an overview of the major longitudinal studies which found an accelerated decline in lung function in diabetic patients.…”
Section: Decline In Lung Function Over Time and Its Clinical Implicationmentioning
confidence: 99%
“…Some longitudinal studies suggested also that the decline of lung function in diabetes mellitus was faster than in normal subjects [79][80][81]. However, a 15-year observation study showed that FEV1 and forced vital capacity (FVC) declined at a comparable rate in diabetics and nondiabetic subjects [82].…”
Section: The Diabetic Lung: Potential Effects On Insulin Absorptionmentioning
confidence: 94%
“…While such a measure should be recommended when trying to define the effects of the drug in a framework free of confounding factors, it limits our knowledge of the usefulness and safety of inhaled insulin since it excludes not only patients with an obstructive respiratory disease, but also patients with a restrictive functional pattern. Indeed, diabetes mellitus is associated with accelerated decline of dynamic lung volumes, and FEV1 decreases in restrictive conditions [79][80][81]110]. Thus, longstanding diabetes likely becomes itself a criterion of exclusion from these studies.…”
Section: )mentioning
confidence: 99%
“…Both peripheral and central chemosensitivity to hypoxia is altered, as is the bronchomotor tone in lung. The coexistence of this finding with other risk factors like lung microvascular complications, endocrine impairments, obesity, and hypertension, lead to a higher prevalence of sleep apnea syndrome (SAS) in diabetic patient ( 18 , 19 ). Clinical implications of SAS go from a decrease in quality of life due to sleepiness to an increased risk of sudden death ( 20 ).…”
Section: Definitionmentioning
confidence: 99%